2023
DOI: 10.1007/s00392-023-02261-w
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to oral anticoagulation measured by electronic monitoring in a Belgian atrial fibrillation population

Abstract: Introduction Stroke prevention using oral anticoagulation (OAC) is the first management priority in atrial fibrillation (AF). Despite the importance of good therapy adherence, real-world adherence is still suboptimal. Patient education and adherence monitoring with new technologies are recommended. The main purpose of this sub-analysis of the AF-EduCare trial was to evaluate the effect of personalized follow-up strategies on adherence to OAC. Methods Regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A higher rate of thrombus resolution might have been achieved through longer anticoagulation or by switching between anticoagulants in selected patients [ 2 , 18 , 21 ]. In this context it is of interest that 16.8% of the study patients were already receiving anticoagulation for other indications at the time of LV thrombus diagnosis, a fact that is not well established in the literature [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…A higher rate of thrombus resolution might have been achieved through longer anticoagulation or by switching between anticoagulants in selected patients [ 2 , 18 , 21 ]. In this context it is of interest that 16.8% of the study patients were already receiving anticoagulation for other indications at the time of LV thrombus diagnosis, a fact that is not well established in the literature [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome parameter of the AF-EduApp study was to improve therapy adherence to oral anticoagulation (OAC) by using this educational smartphone application with an integrated medication list and reminders. The results showed that patients who installed a medication reminder had a higher therapy adherence to OAC than those patients who used the app but did not install a medication reminder ( 14 ). Other outcome parameters such as AF knowledge, self-care capabilities, AF symptom burden and quality of life are expected in the first half of 2024.…”
Section: Introductionmentioning
confidence: 99%